2019
DOI: 10.3390/biom9090420
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Small-Molecule Compounds in Plant Adventitious Root Development

Abstract: Adventitious root (AR) is a kind of later root, which derives from stems and leaf petioles of plants. Many different kinds of small signaling molecules can transmit information between cells of multicellular organisms. It has been found that small molecules can be involved in many growth and development processes of plants, including stomatal movement, flowering, fruit ripening and developing, and AR formation. Therefore, this review focuses on discussing the functions and mechanisms of small signaling molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 67 publications
(164 reference statements)
0
7
0
Order By: Relevance
“…In addition, various small-molecule compounds such as nitric oxide (NO), hydrogen gas (H 2 ), hydrogen sulfide (H 2 S), methane (CH 4 ) and hydrogen peroxide (H 2 O 2 ), are also involved in adventitious root formation and development [17]. According to the present evidence, H 2 O 2 mainly acts to stimulate adventitious root formation.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…In addition, various small-molecule compounds such as nitric oxide (NO), hydrogen gas (H 2 ), hydrogen sulfide (H 2 S), methane (CH 4 ) and hydrogen peroxide (H 2 O 2 ), are also involved in adventitious root formation and development [17]. According to the present evidence, H 2 O 2 mainly acts to stimulate adventitious root formation.…”
Section: Introductionmentioning
confidence: 75%
“…In this study, 44 putative RBOH genes were identified from six horticultural Rosaceae species; their numbers ranged from a minimum of 4 to a maximum of 10 in the Rosaceae genomes (Table 1). Among the RBOHs surveyed in a wider group of plants, the maximum number was found in the soybean genome (17), while the minimum number was found in sweet cherry (4). A comparison of RBOH numbers in 18 species (Fig 1A) indicated that the expansion of the RBOH gene family was not associated with an increase in the total number of predicted genes in a genome.…”
Section: Discussionmentioning
confidence: 96%
“…The formation of adventitious roots can expand plant root systems and give plants and cells the ability of regeneration. Study has shown that traditional plant hormones and small gaseous molecules, as signal molecules, participate in adventitious rooting [ 3 ]. Therefore, in-depth study of adventitious roots will help us to clarify the mechanism of plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent reviews have summarized the roles of steroidal phytohormone BRs in plants, which were mainly involved in the discovery of BRs and hormonal interactions in plant development and stress adaptation [ 8 , 22 ]. The roles of SMCs in adventitious rooting have also been reviewed [ 23 ]. However, the crosstalk between BRs and SMCs in plant growth and stress responses remains to be explored and reviewed.…”
Section: Introductionmentioning
confidence: 99%